Properties of Amorphous Silica Synthesized from Copper-Smelting Slags - Kurbanov, M. Sh.; Tulaganov, S. A.; Ernazarov, M.; Andriyko, L. S.; Marynin, Andriy; Shevchenko, Oleksandr (My University, 2021)
Highly dispersed powders of amorphous silica (silicon dioxide) with a purity of 99.98 % using ammonium fluoride were synthesized from the man-made waste of copper-smelting production. The amorphous state of the obtained silica samples was confirmed by XRD analysis. It was found that the particle size distribution of SiO2 in an aqueous medium is mainly represented by aggregates (100-220 nm) and agglomerates of aggregates (1300 and 5500 nm). It is shown that an increase in the time of ultrasonic treatment does not significantly affect the bi- or trimodal character of the particle size distribution. The effective diameter Def of agglomerates of silica particles decreases by 3 times during the first 10 min of ultrasonic treatment. With a subsequent increase in the processing time, Def does not change significantly, but fluctuates around some specific value. IR spectra of silica samples have characteristic bands related to bending vibrations of Si–O–Si at 468 cm – 1 (intense) and O–Si–O at 800 cm – 1 (average intensity), as well as bands related to stretching vibrations of Si–O–Si in the range 1000-1200 cm – 1, which are responsible for the reactivity. It was found that the process of thermal desorption from the surface of the SiO2 sample proceeds in several stages, with the most intense release of the following main volatile products: O (m/z 16), OH (m/z 17), H2O (m/z 18), and CO (m/z 28). The textural characteristics of the synthesized powders were determined by the method of low-temperature nitrogen adsorption. It is shown that the shape of the adsorption isotherm and the hysteresis loop corresponds to the texture porosity of aggregates of non-porous nanomaterials. The adsorption isotherm is well linearized, which made it possible to calculate the specific surface area according to BET (64 m2/g) and Langmuir (93 m2/g), the total pore volume, micropores, and the total area of micropores.
Keywords: synthesis; ammonium fluoride; industrial waste; silicon dioxide; particle size distribution; синтез; фторид амонію; промислові відходи; високодисперсні порошки; кремній діоксид; кафедра процесів і апаратів харчових виробництв; кафедра технологічного обладнання та комп’ютерних технологій проектування